LinProT: the feasibility of a multimedia courseware for optimization methods course - Raja Noor Farah Azura Raja Maamor Shah (Tanjong Malim, 2019)
LinProT: the feasibility of a multimedia courseware for optimization methods course by Raja Noor Farah Azura Raja Maamor Shah